Prediction of Drug Addiction level Using Matlab Software Application in Batam : Prediksi Tingkat Kecanduan Terhadap Narkoba Menggunakan Aplikasi Software Matlab Dikota Batam - Very Karnadi (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
Batam City is currently very dangerous in drug cases both in the field of dealers and users. The government has issued a statement about the Narcotics Emergency. Seen many who consume drugs do not look at age, starting school children and adults. The purpose of this study is to determine the level of drug use so that the way to overcome it. The benefits of this research are so that users can avoid drugs because they already know the negative effects of drug use. This fuzzy application method uses the Sugeno method by applying the max-min value and producing linear constants. The rare steps of the Sugeno method are the formation of the fuzzy set, the application of the implication function, the composition of the rules, and the affirmation (defuzzification). The input variables in this study were displeased, indifferent, memory impairment, red-eye and lazy moving and output level of addiction so as to get a final value decision support system. The results of this study can be used as a reference for people who use drugs and as a notification to the Batam community about the dangers of consuming drugs.